Fermentasi Tape dan Minas dalam Perspektif Hukum Islam - Asri, Asri; Ihwan Wahid Minu; Riska, Riska; Raihanah Rahmat (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2021)
This study aimed to analyze the position of tape and minas in the perspective of Islamic law, starting from the manufacturing process to its form into fermented food and drinks. This research was a qualitative research with a legal-formal approach to analyze the legal status of halal and haram fermentation of tape and minas. The results showed that the process of making tape and minas used a non-alcoholic fermentation system, namely fermentation that does not aim to form high levels of alcohol by using certain alcohol so that the element of haram is not found in the manufacturing process. In terms of legal status, the existence of tape and minas is seen from the aspect of the substance contained in the form of ethanol as part of high alcohol content. In terms of legal status, the existence of tape and minas is seen from the aspect of the substance contained in the form of ethanol as part of high alcohol content.